Patrioci krytyczni kontra mitomani. Walka o politykę historyczną w obliczu Grossa - Misiewicz, Agnieszka (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Patriotism is one of the concepts that cannot be easily interpreted. It can be seen at least two models of patriotism - „critical”, which draws attention also to the shameful experience and „conservative”, associated with the myth of proud and suffering of the Polish nation, connected also with a specific historical policy. Visible manifestation of these extreme camps are public debates on the publications of J. T. Gross, showing the Poles as perpetrators of suffering and death of many Jews.